Sarcocystis spp.: histological examination and morphometry - V. V. Stafford (Российский паразитологический журнал, 2023)
The purpose of the research is localization and morphometry of sarcocysts in animals.Materials and methods. Samples of striated muscle tissue of cows and wild boars were studied to determine the infection intensity and prevalence and determine morphometric parameters of cysts. Pathological material was collected to 10 % buffered formalin solution. For histological examination, muscle tissue samples were taken from the abdominal wall and cardiac muscle. To process tissue samples, paraffin coating was used in semi-automatic equipment from Thermo Scientific. Histological specimens were stained with hematoxylin and eosin and by Mallouri. The specimen histoarchitecture was assessed using an Axio A1.0 microscope; photographs were taken with AxioVision.Results and discussion. The sarcocyst infection prevalence was 60% in cattle and 100% in the boars, with the infection intensity of 1-2 and 2-4 sarcocysts in one FOV, respectively. It was found that the cyst formed a capsule in infected boars with a thickness of 2.6±0.28 μm, while it was practically invisible in cattle, and grouped loose connective tissue fibers were observed around the cyst. The infection intensity can be assessed as low in the studied animals; however, even single parasite cysts entered the human body contribute to sarcocystosis.